Modelling and simulation of uninterruptable power supply (UPS) system with power factor correction (PFC) using MATLAB/Simulink - Ahmad, Anwarudin (2010)
This thesis presents a modelling and simulation of UPS system with power factor correction (PFC) using MATLAB/Simulink (MLS). The purpose of this project is to investigate and understand the UPS system with PFC with the main focus on modelling and simulaton. This work focus on the effect of PFC that function to correct the supply current to become in phase with the voltage at the input side of the rectifier. All part of the model is design to be reliable and synchronies to each other henceforth make the overall system efficient in term of losses and harmonic. This modeling and simulation will be contributing to major improvement to the work of others on power electronics field.